(untitled) (Journal of Scientific Research, 2016)
Incubation experiments were carried out to determine the effect of eutrophication on carbonate dissolution under high pCO2 (partial pressure of carbon dioxide) condition in coral reef ecosystem at Sesoko Island, Okinawa, Japan. Short incubation (24 h under natural illumination) and long incubations (4 days under dark condition) were carried out using white coral skeleton (without attachment of living organism, control); natural rubble (with associated epilithic and endolithic communities) and natural rubble with addition of dissolve organic matter (glucose and coral mucus). Addition of DOM significantly enhanced bacterial abundance (t-test; p=0.01) and net respiration (t-test; p=0.0001) with increasing pCO2 levels (p < 0.05) under natural illumination. Consistent with increase in respiration, dissolution rates also increased from 136.22±2.04 to 652.38±4.51 µmolm-2d-1. Under dark condition, where photosynthesis was inhibited, dissolution of calcium carbonate further increased with addition of different level of DOM. In addition of DOM incubation bottles, bacterial abundance increased by 3 4 orders of magnitude and the dissolution rates increased by 2.5 10 times more than the control. The results suggest that availability of organic matter in the reefs will enhance metabolic activities (respiration) of microbial communities associated with coral rubble which ultimately increase dissolution of calcium carbonate.